Antibacterial activity testing of ethanolic extract of aloe vera leaf and gel against methicillin-resistant Staphylococcus aureus - Pratiwi, Tias Eka; Dewi, Warta; Prijono, Eddy (Padjadjaran Journal of Dentistry, 2014)
Introduction: The interest on Aloe vera based herbal products is fast growing during recent years, particularly in medication regarding their antibacterial properties which had a lot of active components such as saponin and anthraquinone. Methicillin-resistant Staphylococcus aureus has emerged as one of the most important human pathogens causing nosocomial infections and became the first priority as a consequence of their resistancy. The purpose of this study is to determine the minimum levels of ethanol extract of leaves and Aloe Vera gel that can inhibit MRSA and find out whether there are differences in antibacterial power between of ethanol extract of leaves and Aloe Vera gel. Methods: Ten isolates of MRSA were investigated for their sensitivity to Aloe vera leaf and gel extract using the serial dilution method by doing two times repetition and statistically analyzed according to t-test method. Result: The result shows that the Minimum Inhibitory Concentration of Aloe vera leaf and gel extract each located at a concentration of 25% and 12,5%. There is a significant difference in antibacterial power between the ethanol extract of leaves and Aloe Vera gel in inhibiting MRSA with MIC values of 25% and 12.5% Conclusion: There was a difference between Aloe vera leaf and gel extract antibacterial activity, where the gel extract is more effective than leaf extract.